A Spatial-Based Planning Analysis for Transmission Line Development Using the Multi-Criteria Decision Analysis (MCDA) Approach - Anam, Juzd Thoha Chairul; Muzaki, Anggi Afif; Garnierita Simanjuntak, Rinovia Mery (Riviera Publishing, 2025)
Through the Electricity Supply Business Plan (RUPTL) 2021–2023, PT PLN (Persero) outlined plans for the development of transmission systems across Indonesia, projecting an expansion of 76,662 MVA in substation capacity and 47,723 kilometres of transmission lines by 2030. Transmission infrastructure development is further detailed for each major island system in the country. In particular, the transmission network in Sulawesi remains divided into two systems: Southern Sulawesi (SULBAGSEL) and Northern Sulawesi (SULBAGUT). The RUPTL document also highlights several strategic projects in the Sulawesi transmission system, including the 150 kV Tambu–Bangkir Transmission Line. Following an instruction from the Directorate General of Electricity to accelerate the Commercial Operation Date (COD) for the Tambu–Bangkir segment to 2024, the project timeline has been adjusted accordingly and designated as a priority assignment. Current transmission line construction planning still relies on manual methods, which have several weaknesses, including route inefficiency, potential cost overruns, challenges in accessing planning locations, and low planning accuracy that often does not reflect actual field conditions. This approach also inadequately considers disaster factors and the aspects of environmental, social, and corporate governance. This research aims to develop a more effective and efficient method for transmission line planning that reduces cost overruns while improving accessibility and planning accuracy. Additionally, this study will explore ways to incorporate land use, road access, disaster factors, and environmental, social, and corporate governance considerations. Spatial modeling using the Multi-Criteria Decision Analysis (MCDA) method can offer a more comprehensive approach, making transmission line planning more optimal and sustainable.